Utility of a next‐generation framework for assessment of genomic damage: A case study using the pharmaceutical drug candidate etoposide. (22nd November 2021) - Nicolette, John; Luijten, Mirjam; Sasaki, Jennifer C.; Custer, Laura; Embry, Michelle; Froetschl, Roland; Johnson, George; Ouedraogo, Gladys; Settivari, Raja; Thybaud, Veronique; Dearfield, Kerry L.
Abstract: We present a hypothetical case study to examine the use of a next‐generation framework developed by the Genetic Toxicology Technical Committee of the Health and Environmental Sciences Institute for assessing the potential risk of genetic damage from a pharmaceutical perspective. We used etoposide, a genotoxic carcinogen, as a representative pharmaceutical for the purposes of this case study. Using the framework as guidance, we formulated a hypothetical scenario for the use of etoposide to illustrate the application of the framework to pharmaceuticals. We collected available data on etoposide considered relevant for assessment of genetic toxicity risk. From the data collected, we conducted a quantitative analysis to estimate margins of exposure (MOEs) to characterize the risk of genetic damage that could be used for decision‐making regarding the predefined hypothetical use. We found the framework useful for guiding the selection of appropriate tests and selecting relevant endpoints that reflected the potential for genetic damage in patients. The risk characterization, presented as MOEs, allows decision makers to discern how much benefit is critical to balance any adverse effect(s) that may be induced by the pharmaceutical. Interestingly, pharmaceutical development already incorporates several aspects of the framework per regulations and health authority expectations. Moreover, we observed that quality dose response data can be obtained with carefully planned but routinely conducted genetic toxicity testing. This case study demonstrates the utility of the next‐generation framework to quantitatively model human risk based on genetic damage, as applicable to pharmaceuticals.